An Efficient Artificial Intelligence (Al) and Blockchain-Based Security Strategies for Enhancing the Protection of Low-Power loT Devices in 5G Networks - Ibrahim Akmal; Hamayun Khan; Ayesha Khushnood; Fatima Zulfiqar; Eman Shahbaz (Spectrum of Engineering Sciences, 2024)
Today, the ever-growing Internet of Things revolutionizes the face of digital connectivity. IoT devices are proliferating while 5G networks are constantly being deployed all over the world. All these new developments bring the problem of privacy concern for these low consumption, less computational IoT devices. This paper details an advanced security framework for the protection of those devices by integrating AI and blockchain but in focus on real-time anomaly detection and decentralized data integrity. This research will employ systematic literature review to determine the current solutions that reveal AI-based solutions for network anomaly detection and blockchain to secure data without central control. It will adapt AI to ensure the best threat detection and protection through blockchain for the best possible protection of data against attacks like unauthorized access and DDoS attacks. The combination of AI and blockchain seems to represent a good solution for 5G securing the Internet of Things by creating a balance between protecting data and energy efficiency. The limits of the power of computational devices indicate further refinements in these technologies at scale. The future agenda of research should target at reducing the computational demands along with standards to be created for unified IoT security. Therefore, the frameworks compared in this paper review is efficient and secure in supporting a future-proof 5G-ready IoT ecosystem against emerging threats and supports high interconnectivity Keywords: IoT devices, Networking, 5G, AI, blockchain, low-power IoT devices, decentralized security, Blockchain.